Hematopoietic stem cell transplantation for non-Hodgkin lymphoma in Brazil: real-life data - Hallack Neto, Abrahão Elias; Simione, Anderson; Sabaina , Paula; da Silva, Cinthya; Barroso, Fernando; Barros, George; Vigorito, Afonso; Colella, Marcos; Nabhan, Samir; Funke, Vaneuza; et al. (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2023)